Nonlinear relationship between enteric-coated mycophenolate sodium dose and mycophenolic acid exposure in Han kidney transplantation recipients - Jun Zhang; Mengmeng Jia; Lihua Zuo; Na Li; Yonggang Luo; Zhi Sun; Xiaojian Zhang; Zhenfeng Zhu (Elsevier, 2017)
The aim of the research was to investigate the pharmacokinetics (PK) of enteric-coated mycophenolate sodium (EC-MPS) by quantification of the active metabolite of mycophenolic acid (MPA) after multiple escalating oral doses in Han kidney transplant recipients. A total of 28 Han postoperative kidney transplant recipients were given a multiple-dose of 540, 720 or 900 mg of EC-MPS two times a day in combination with tacrolimus for 6 days. Blood specimens were collected at each time point from 0 to 12 h after EC-MPS administration. MPA plasma concentrations were measured by UPLCUV. The relationship between the EC-MPS dose and its PK parameters was assessed. In the range from 540 to 900 mg, Cmax and AUC012h did not increase with dose escalation. The AUC012h, Cmax, C0 and Tmax for the 540 720 and 900 mg doses were not significantly different, respectively (P >0.05). AUC012 h and Cmax were increased less than proportionally with increasing EC-MPS dose levels. Inter-individual variability in AUC012h, Cmax and C0 were considerable. Nonlinear PK relationships were found from the doses of 540-900 mg of EC-MPS.